THE IMPACT OF A TEACHER'S SPEAKING SPEED AND PRONUNCIATION ON STUDENT PERCEPTION (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2025)
This article examines the impact of a teacher’s speech rate and pronunciation on students’ perception and comprehension. It highlights how speech speed, clear articulation, and intonation affect students’ understanding, attention, and learning outcomes. The study emphasizes the importance of balanced speech pace, proper pronunciation, and expressive intonation in effective teaching.